1991
DOI: 10.1099/00222615-35-5-278
|View full text |Cite
|
Sign up to set email alerts
|

Identification of enteropathogenic Escherichia coli isolated in Britain as enteroaggregative or as members of a subclass of attaching-and-effacing E. coli not hybridising with the EPEC adherence-factor probe

Abstract: I d e n t if i ca t i o n of en t e ro p a t h oge n i c Escherichia co/iSummary. Strains of Escherichia coli from sporadic cases of diarrhoea and belonging to serotypes 044 : H 18,055 : H7,O 1 1 lab : H2 1,011 1 ab : H25 or 0 126 : H27 were examined for virulence properties. With the exception of 0 1 1 lab: H25 these are considered to be classical enteropathogenic E. coli (EPEC) serotypes. The strains had been isolated in Britain from the faeces of children < 3 years old. Of the serotypes examined, 7 of 13 04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
74
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 5 publications
7
74
0
Order By: Relevance
“…It is interesting that enteroaggregative strains of E. coli (EAggEC) have been implicated epidemiologically as one of the aetiological agents of diarrhoea [12-141. Even in EPEC serogroups, it has been suggested that EAggEC strains are probably more important than those which are EAF-positive [15]. On the other hand, it has also been proposed that some E. coli strains showing 'diffuse adherence' (DAEC) also K. TAMURA E T A L .…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that enteroaggregative strains of E. coli (EAggEC) have been implicated epidemiologically as one of the aetiological agents of diarrhoea [12-141. Even in EPEC serogroups, it has been suggested that EAggEC strains are probably more important than those which are EAF-positive [15]. On the other hand, it has also been proposed that some E. coli strains showing 'diffuse adherence' (DAEC) also K. TAMURA E T A L .…”
Section: Discussionmentioning
confidence: 99%
“…The finding that 0126:H10, categorised as EAggEC, is noteworthy in the light of the recent report by Scotland et al that the EPEC strains of serotype 0126: H27, obtained from patients with diarrhoea in the UK, were in fact EAggEC. 39 Further study of E. coli as a diarrhoea1 agent depends on increased understanding of the pathogenesis of the disease. This study presents the results of comprehensive screening of virulence factors in diarrhoeagenic E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…H21 and a single isolate of 055. H4 have previously been shown to exhibit enteroaggregative E. coli (EAggEC) adherence characteristics and to hybridize with the EAggEC probe [48,49].…”
Section: Allele Specific Pcrmentioning
confidence: 99%